2021
DOI: 10.1007/s00251-021-01204-x
|View full text |Cite|
|
Sign up to set email alerts
|

Major histocompatibility complex (MHC) associations with diseases in ethnic groups of the Arabian Peninsula

Abstract: Since the discovery of human leukocyte antigens (HLAs), the function of major histocompatibility complex (MHC) gene families in a wide range of diseases have been the subject of research for decades. In particular, the associations of autoimmune disorders to allelic variants and candidate genes encoding the MHC are well documented. However, despite decades of research, the knowledge of MHC associations with human disease susceptibility have been predominantly studied in European origin, with limited understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 119 publications
0
13
0
Order By: Relevance
“…Given that the non-Qatari Middle Eastern group comprises nationals from Egypt, Sudan, Syria, Iran, and Yemen ( Table S5 ), it seems possible that genetic differences between the Qatari and non-Qatari Middle Eastern groups might underpin the apparently decreased magnitude of humoral responses following infection and increased risk of COVID-19 disease observed here for the Qatari group. While we did not have access to genome sequence data for this cohort to verify this, it is perhaps relevant that the Qatari population has been reported to have an elevated prevalence of common adult diseases [ 38 ], as well as of childhood autoimmune diseases such as type 1 diabetes [ 39 ], potentially suggestive of uncharacterized genetic factors that affect humoral immune responses through HLA allelic variation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the non-Qatari Middle Eastern group comprises nationals from Egypt, Sudan, Syria, Iran, and Yemen ( Table S5 ), it seems possible that genetic differences between the Qatari and non-Qatari Middle Eastern groups might underpin the apparently decreased magnitude of humoral responses following infection and increased risk of COVID-19 disease observed here for the Qatari group. While we did not have access to genome sequence data for this cohort to verify this, it is perhaps relevant that the Qatari population has been reported to have an elevated prevalence of common adult diseases [ 38 ], as well as of childhood autoimmune diseases such as type 1 diabetes [ 39 ], potentially suggestive of uncharacterized genetic factors that affect humoral immune responses through HLA allelic variation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…MHC-I region contains a large number of immune-related genes, which are often polymorphic and closely linked as a result of their genomic proximity ( 6 ). In addition, many of these genes are associated with infections and autoimmune diseases, such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) ( 6 ).…”
Section: Cluster Of E3 Ubiquitin Ligases Genes In the Mhc-i Regionmentioning
confidence: 99%
“…MHC-I region contains a large number of immune-related genes, which are often polymorphic and closely linked as a result of their genomic proximity ( 6 ). In addition, many of these genes are associated with infections and autoimmune diseases, such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) ( 6 ). The human MHC-I genomic region locates on chromosome 6p21.33-6p22.2, known as human leukocyte antigen (HLA) class I region which contains HLA gene loci and several non-HLA gene clusters ( 7 ).…”
Section: Cluster Of E3 Ubiquitin Ligases Genes In the Mhc-i Regionmentioning
confidence: 99%
“…Patients of Arabian ancestry share several MHC haplotypes which confer either susceptibility or protection to T1D with other ethnic groups ( Al Naqbi et al, 2021 ). However, there are also other disease-associated MHC haplotypes in Arabs that are distinct from other ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…HLA-DR3 and HLA-DR4 appears the most common subtypes in T1D disease association studies involving Arabian populations ( Al-Hussein et al, 2003 ; Al-Harbi et al, 2004 ; Al-Jenaidi et al, 2005 ; Al-Herbish et al, 2008 ). However, there are a number of ethnic specific differences ( Al Naqbi et al, 2021 ). Of note, a study by Hajjej et al (2018) reported that HLA-DRB1 ∗ 03/HLA-DRB1 ∗ 04 genotype showed the highest risk of T1D development ( Hajjej et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%